Proses Penyelesaian Perkara Wanprestasi Atas Jual Beli Gamelan (Studi Kasus di Pengadilan Negeri Karanganyar) - Saputra, Adi Candra; , Nuswardhani, S.H, S.U (2017)
There is a case of defaults on the purchase contained in the purchase agreement gamelan. This study aims to determine the buying and selling process gamelan and settlement process of buying and selling gamelan until there demands of default by the plaintiff or the buyer, to find out the considerations in determining the evidence and the judge in determining the verdict on the case of default in sale and purchase of gamelan. The research method using descriptive normative approach. Using this type of primary data and secondary data. Data collection techniques used through the study of literature, documentation, questionnaires and interviews. The results showed that the process of buying and selling gamelan originated from a buyer booked gamelan to the craftsman gamelan, the process of settlement of buying and selling gamelan until there demands tort committed by the defendant that the ordering of goods is not within specifications and behind schedule submission, consideration of the judge looks at the process of evidence in court by documentary evidence and witnesses proved that the first defendant and the second defendant declared in default, at the hearing the plaintiff can prove the arguments of the lawsuit while defendant I and defendant II can not prove rebuttal, the plaintiff is granted in part, the defendant was sentenced to pay compensation to the plaintiff.